Factores biosocioculturales y calidad de cuidados de enfermería en adulto mayor hospitalizado en Clínica Madre de Cristo - Rivera Pacheco, Delfina Azucena (2021)
This descriptive, cross-sectional correlational investigation was carried out with the purpose of determining the relationship between biosociocultural factors and quality of nursing care in the elderly hospitalized at the Madre de Cristo Clinic. The instruments of biosociocultural factors and the CARE Q nursing care quality questionnaire were applied to 30 older adult patients, using the Chi-square statistical test, concluding: 63% are between 60 and 70 years old, 60% are women, 53% have no education, 57% come from the sierra region. In the dimensions it is accessible and explains and facilitates, 73% and 70% respectively refer to medium care quality, 60% medium care quality in the comfort dimension and 30% high quality of care in this dimension, 73% in the This dimension anticipates and maintains relationships of trust, 57% report medium quality of care, in the monitoring and follow-up dimension, and 43% high in this dimension. In the dimension, it is accessible, a significant relationship is found between age p = 0.001 and the degree of education p = 0.094 with the average quality of care. In the dimension, it explains and facilitates a significant relationship between age p = 0.028, Degree of education p = 0.071 and the average quality of care. In the Comfort, monitor and follow-up dimensions, it shows a significant relationship between age p = 0.048, p = 0.050 respectively with the average quality of care.